IoT Application of Simple Solar Intensity Monitoring System Using Photovoltaic Panel - Lestari, Resma Puji; Yuliza, Elfi; Ekawita, Riska (JPSE (Journal of Physical Science and Engineering), 2023)
Solar radiation data is useful for solar power plant (PLTS) development, the agricultural sector, renewable energy, transportation and communication, and other disciplines. This data is generally obtained from government agencies. The device used to measure solar radiation is a pyranometer. However, this equipment has limited availability and the data information is only owned by certain regions. Therefore, it is necessary to develop a simpler measuring instrument for the intensity of solar radiation. So that data information is obtained easily and the operation of tools is easy. In this study, photovoltaic panels were used to read the intensity of solar radiation. When this panel is exposed to the sun it will generate electricity and its output is proportional to its radiation. Data monitoring utilizes IoT. The measured results of measuring the intensity of solar radiation have a maximum value of 450.21 W/m2. The measured magnitude of the solar radiation value shows that the influence factors in the form of sunlight intensity, ambient temperature, and panel output power are proportional to the radiation value while environmental humidity is inversely proportional to the radiation value.